The structural plasticity of Tom71 for mitochondrial precursor translocations - Li, Jingzhi (International Union of Crystallography, 2010)
Mitochondrial precursors are transported through the translocase of the outer membrane (TOM) complex. Tom70/Tom71 is a major surface receptor of the TOM complex for mitochondrial precursors and facilitates Hsp70/Hsp90-escorted precursor translocation into the mitochondrion. Previous structural studies of Tom71 have revealed that it contains an N-terminal and a C-terminal domain and that the two domains may remain in an open conformation when binding to Hsp70/Hsp90. In a newly obtained crystal form of a complex of Tom71 and the Hsp70 C-terminus, the N-terminal domain was found to have rotated about 12° towards the C-terminal domain compared with the previous determined crystal structure of Tom71 in the open conformation. This newly solved structure is defined as the ‘intermediate conformation’. The domain rearrangements in Tom71 significantly change the surface hydrophobicity and the volume of the precursor-binding pocket. This work suggests that Tom70/Tom71-family members may exhibit structural plasticity from the intermediate conformation to the fully open conformation when complexed with Hsp70/Hsp90. This structural plasticity enables the precursor receptors to accommodate different precursor substrates for mitochondrial translocation.